Main fatty acids, phenolic compounds, and evaluation of gastroprotective effect of malbec grape seeds, a wine industry by-product - Gonzales, M.; Chávez-Flores, J.E.; Obregón-Tinoco, H.; Cárdenas-Toro, F.P.; Simirgiotis, M.J.; Bórquez, J.; Robles Caycho, J. (Rasayan Journal of Chemistry, 2020)
Grape seeds are the main winemaking by-product, which has a high content of bioactive compounds. This study aims to evaluate the profile of fatty acids and phenolics of grape seeds (an organic waste), obtained from a Peruvian wine factory; the antioxidant activity and the gastroprotective effect of alcoholic extracts were also determined. The oil extraction yield was 14.8%, mainly composed of linoleic (71.6%) and oleic (17.4%) acids. Furthermore, 22 phenolic compounds in the methanolic extract were identified by UHPLC-Q/Orbitrap/MS/MS, being the flavan-3-oles and procyanidins the major components. The content of phenolics and the antioxidant activity (IC50) were 40.03 0.36 mg of GAE/g of dry seed and 15.31 0.03 g/mL respectively. The methanolic extract of grape seeds exhibited a great gastroprotective effect against gastric ulcers induced by naproxen, achieving 80% inhibition at a dose of 600 mg/kg. Base on the results, the grape seeds are a potential source of bioactive compounds, and their use is an alternative for the prevention of gastric ulcers.
Keywords: Wine; Grape wine; Grape seed; Chemistry; Product (mathematics); Food science; Mathematics; https://purl.org/pe-repo/ocde/ford#4.03.03